The Effect Of Emotional Intelligence And Organizational Culture On Organizational Commitment Through Job Satisfaction As Intervening Variable In PT.Capella Multidanda - Angelita, Indah; Syaifuddin, Syaifuddin; Faris, Salman (International Journal of Science, Technology & Management, 2022)
This study aims to analyze the influence of emotional intelligence and organizational culture on organizational commitment through job satisfaction as an intervening variable at pt. capella multidana. The population in this study was 492 people, with a sample of 81 people at a 90% confidence interval. The technique used in sampling is purposive sampling. The data analysis tool uses SPSS. The results of the analysis show that emotional intelligence has a positive and insignificant effect on job satisfaction at PT. Capella Multidana. Organizational culture has a positive and insignificant effect on job satisfaction at PT. Capella Multidana. Emotional intelligence has a positive but not significant effect on organizational commitment at PT. Capella Multidana. Organizational Culture has a positive and insignificant effect on organizational commitment at PT. Capella Multidana. Job satisfaction has a positive but not significant effect on organizational commitment at PT. Capella Multidana. The direct effect of emotional intelligence on organizational commitment is smaller than the indirect effect of emotional intelligence on organizational commitment. The direct effect of organizational culture on organizational commitment is smaller than the indirect effect of organizational culture on organizational commitment.